2019
DOI: 10.1007/s40094-019-00350-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma oxidation parameters on physical properties of nanocrystalline nickel oxide thin films grown by two-step method: DC sputtering and plasma oxidation

Abstract: Nanocrystalline nickel oxide (NiO) thin films were successfully grown on quartz substrates by two-step method. In the first step, nickel films were deposited on quartz substrates by DC magnetron sputtering technique. Then, the plasma oxidation of nickel films was used for preparation of nickel oxide. The effect of DC plasma power and treatment time on the structural, morphological and optical properties of the NiO films were investigated by different analyses. XRD results indicated that the plasma powers effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Therefore, the crystalline peaks appeared in the XRD patterns of the as-prepared coatings are associated to Ni ( Fig. 2a, the intensity of peaks increases suggesting the increase in the grain size by increasing the plasma power 28,29 . The major XRD peaks of electrode No.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, the crystalline peaks appeared in the XRD patterns of the as-prepared coatings are associated to Ni ( Fig. 2a, the intensity of peaks increases suggesting the increase in the grain size by increasing the plasma power 28,29 . The major XRD peaks of electrode No.…”
Section: Resultsmentioning
confidence: 98%
“…By comparing the SnO 2 films obtained from two deposition methods, unbiased and biased, it was found that the unbiased films possess better sensitivity and electrical properties. Hajakbari et al 77 and Rashvand et al 78 used a two-step method to prepare nickel oxide nanofilms on quartz substrates by first depositing nickel films on the substrates using a DC magnetron sputtering technique and then using different powers of DC oxygen plasma to oxidize the nickel films at different times to obtain nickel oxide films. Fig.…”
Section: Transition Metal Hybridsmentioning
confidence: 99%
“…3 XRD spectra of NiO films grown on quartz substrates under plasma treatment (a power and b time). 77…”
Section: Activated Carbonsmentioning
confidence: 99%
“…Earlier reports have demonstrated that oxygen plasma treatment can be effectively used for the formation of metal-oxide thin films on metal surfaces and for the surface cleaning of metallic thin films, by reducing the surface roughness. 27,[33][34][35][36][37] By adjusting the electrode deposition rate and optimizing the oxygen plasma treatment conditions, a drastic change is observed in the electrical characteristics. This is manifested by a gradual variation in the current with the applied bias, possibly owing to the change in the transport mechanism.…”
Section: Surface Effects On Resistive Switchingmentioning
confidence: 99%